Microbiostratigraphy and Sedimentary Environment of the Sarvak and Kazhdumi Formations in Bahregansar Oil Field - Ahmadi, Somayeh; Vaziri, Seyed Hamid; Khaksar, Keyvan; Jahani, Davood; Ali, Mohsen Ale (International Journal of Geography and Geology, 2017)
The aim of this paper is investigation of microbiostratigraphy and sedimentary environment of the Sarvak and Kazhdumi formations in Bahregansar oil field. To investigate these units, microbiostratigraphy and microfacies analyses were carried out on nearly 600 m of cuttings, including cutting plug samples and thin sections prepared from Bahregansar oil field in the Persian Gulf, SW Iran. 22 Species and genera of foraminifera were recognized and four biozones were identified. Also the microfacies analysis of the Sarvak and Kazhdumi formations in Bahregansar oil field is led to recognition fourteen microfacies of three facies belts (depositional environment) including open marine, bar and lagoon environments.